Do Cemented Dual-Mobility Cups Confer Stability for Patients at High Risk of Dislocation in Revision Total Hip Arthroplasty? - Evangelista, Perry J.; Okroj, Kamil; Plummer, Darren; Della Valle, Craig J.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2018)
Dislocation is among the most commonly reported complications following revision total hip arthroplasty. Dual-mobility bearings may lower the risk of dislocation. The authors report the results of a multicenter study evaluating the use of a dual-mobility acetabular cup design that was cemented into a metal shell as part of complex acetabular reconstructions or in cases where the risk of dislocation was felt to be high, such as isolated bearing exchanges. Eighteen patients were identified for being at high risk of dislocation who underwent cementation of a dual-mobility shell that is specifically made for cementation, into a fully porous metal revision acetabular cup (10 patients) or into a well-fixed cup at the time of revision without removal of the existing acetabular component (eight patients). Patients were assessed clinically and radiographically at a minimum of 2 years for the evidence of dislocation, revision surgery, and implant loosening. At a mean of 36 months (range, 25–56 months), one patient died and one was lost to follow-up. There were no known cases of hip dislocation. There was one repeat revision, for a deep infection treated with irrigation and debridement. The mean preoperative Harris Hip Score of 46 (range, 40–79) improved to a mean of 65 points (range, 41–97) at the most recent evaluation. Acetabular components were retained in 8 out of 18 cases and the dual-mobility shell was cemented into it. Cementation of a dual-mobility cup into a shell at the time of a revision surgery is a safe and reliable construct at minimum of 2 years for patients at high risk of dislocation. There were no complications related to the cementation of the cup into the metal shell. Longer follow-up is required to further assess the durability of this construct.
Keywords: dual-mobility cup; revision total hip arthroplasty; dislocation; cement